1996
DOI: 10.1074/jbc.271.49.31572
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Multiple Mitogen-activated Protein Kinase Signal Transduction Pathways by the Endothelin B Receptor Requires the Cytoplasmic Tail

Abstract: Endothelin is a 21-amino acid peptide with remarkably diverse biological properties, including potent vasoconstriction, induction of mitogenesis, and a role in the development of blood vessels. In the present study, stimulation of the endothelin B receptor was found to activate three distinct mitogen-activated protein kinase signal transduction pathways, the extracellular regulated kinase (ERK) 2, c-Jun N-terminal kinase 1 (JNK), and p38 kinase. These mitogen-activated protein kinase isozymes are thought to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…In concordance with previous reports, we found that ET-1 activates p38, ERK1/2, and JNK MAPKs (21,41). Early activation of p38 MAPK is required for ET-1 activation of PI3K/AKT, whereas blockade of ERK1/2 or JNK fails to inhibit ET-1 activation of PI3K/AKT.…”
Section: Discussionsupporting
confidence: 80%
“…In concordance with previous reports, we found that ET-1 activates p38, ERK1/2, and JNK MAPKs (21,41). Early activation of p38 MAPK is required for ET-1 activation of PI3K/AKT, whereas blockade of ERK1/2 or JNK fails to inhibit ET-1 activation of PI3K/AKT.…”
Section: Discussionsupporting
confidence: 80%
“…Although the activation of p38 by GPCRs has been documented in primary cells, immortalized cell lines, perfused organs, and even after in vivo manipulations (186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196), there is very limited knowledge on the mechanism of activation of this particular family of MAPKs. The p38α enzyme is activated by both Gα q and Gβγ (197), and a role for the tyrosine kinase Btk in G q -mediated stimulation has been suggested from observations in lymphocytic cells (198).…”
Section: Signaling By G Protein-coupled Receptors To Other Mapk-relatmentioning
confidence: 99%
“…In addition, we previously demonstrated that endothelin B receptor (ETBR) activates Gα13 (6). Gα13 regulates Na/H exchanger activity (7,8), extracellular signal regulated kinase (ERK), c-Jun NH2-terminal kinase (JNK) (9 -11), nuclear factor κB (NF-κB) (12) and the activity of the low molecular weight GTPase, Rho (13 -15), and is also capable of neoplastic transformation, induction of apoptosis, and stimulation of actin reprotein kinases (ERK, JNK, and p38) (23,24). Because of its vasoconstrictor and growth-promoting action, numerous studies indicate that ET-1 is involved in the pathogenesis of a broad spectrum of renal and cardiovascular diseases (21,22,(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%